Editorial: UK quality of care drive improving ulcerative colitis hospital outcomes. Author's reply. Issue 5 (14th August 2019) - Bodger, Keith; ,
Abstract : LINKED CONTENT This article is linked to Shawihdi et al and Moore papers. To view these articles, visit https://doi.org/10.1111/apt.15315 and https://doi.org/10.1111/apt.15412 .